Impact of cluster frontline demonstrations (CFLDs) of oilseeds on productivity and profitability of Gobhi Sarson in Sangrur district of Punjab - Ravinder Kaur; Mandeep Singh; Ashok Kumar Garg (Journal of Oilseed Brassica, 2026)
The study was conducted during Rabi season of 2019-20 and 2020-21 to find out the yield gap between scientificproduction and farmer’s practice under cluster frontline demonstrations (CFLD’s oilseeds) scheme of Gobhi sarson inSangrur district of Punjab. The CFLD’s were conducted with gobhi sarson canola variety GSC 7 of gobhi sarson in 21ha and 10 ha area for two years with active involvement of 104 farmers and technical staff of Krishi Vigyan Kendra,Sangrur. The findings of the study revealed that the highest grain yield was obtained in demonstrated plots with anaverage of 23.23 q/ha as compared to local check (Hyola 401/PBR 91) with an average of 17.98 q/ha. The average meanof extension gap, technology gap and technology index were calculated as 5.25 q/ha, -0.98 q/ha, -4.38, respectively.The demonstrated plots where recommended package of practices for gobhi sarson cultivation were followed endedup with higher B:C ratio (4.05) as compared to farmer’s practice (2.90). Hence, it can be concluded that the productivityof gobhi sarson can be further increased with the cultivation of improved variety GSC 7 along with adoption ofrecommended production practices